Fasting induces hepatic lipid accumulation by stimulating peroxisomal dicarboxylic acid oxidation - Zhang, Xiao (J Biol Chem, 2021)
Fasting induces lipid accumulation in the liver, while the mechanisms by which fasting dysregulates liver fatty acid oxidation are not clear. Fatty acid ω-oxidation is induced in the fasting state, and administration of dicarboxylic acids to fasting animals decreases plasma ketone bodies. We hypothesized that endogenous dicarboxylic acids might play a role in controlling mitochondrial β-oxidation in fasting animals. A peroxisome proliferator-activated receptor-alpha agonist and an inhibitor for peroxisomal β-oxidation were administered to the fasting rats to investigate the role of dicarboxylic acids in liver fatty acid oxidation and lipid homeostasis. We observed that excessive β-oxidation of endogenous dicarboxylic acids by peroxisomes generated considerable levels of succinate in the liver. Excessive succinate oxidation subsequently increased the mitochondrial NADH/NAD(+) ratio and led to an accumulation of 3-OH-CoA and 2-enoyl-CoA intermediates in the liver. This further induced feedback suppression of mitochondrial β-oxidation and promoted hepatic lipid deposition and steatosis. Specific inhibition of peroxisomal β-oxidation attenuated fasting-induced lipid deposition in the liver by reducing succinate production and enhancing mitochondrial fatty acid oxidation. We conclude that suppression of mitochondrial β-oxidation by oxidation of dicarboxylic acids serves as a mechanism for fasting-induced hepatic lipid accumulation and identifies cross talk between peroxisomal and mitochondrial fatty acid oxidation.